K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 1 2019

\(x^3-3x^2-6x+8\)

\(=\left(x^3+8\right)-\left(3x^2+6x\right)\)

\(=\left(x+2\right)\left(x^2-2x+4\right)-3x\left(x+2\right)\)

\(=\left(x+2\right)\left(x^2-2x+4-3x\right)\)

\(=\left(x+2\right)\left(x^2-5x+4\right)\)

\(=\left(x+2\right)\left(x^2-x-4x+4\right)\)

\(=\left(x+2\right)\left[x\left(x-1\right)-4\left(x-1\right)\right]\)

\(=\left(x+2\right)\left(x-1\right)\left(x-4\right)\)

Thiếu đề nha bạn!

_________________

--------------------------------------

^_^

21 tháng 10 2017

a) \(4x^2-12x+9-4\left(x^2-4\right)-x=8\)

\(4x^2-12x+9-4x^2+16-x=8\)

\(-13x+25=8\)

\(-13x=-17\)

\(x=\dfrac{17}{13}\)

21 tháng 10 2017

b) \(\left(3x^3+6x^2\right):3x^2+\left(9x^2-6x\right):0,5x=9\)

\(x+2+18x-12=9\)

\(19x-10=9\)

\(19x=19\)

\(x=1\)

16 tháng 12 2017

a) \(=\left[\left(6x+1\right)+\left(6x-1\right)\right]^2\)

\(=\left(12x\right)^2\)

\(=144x^2\)

a) Ta có: \(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(1+6x\right)\left(6x-1\right)\)

\(=\left(6x+1\right)^2-2\left(6x+1\right)\left(6x-1\right)+\left(6x-1\right)^2\)

\(=\left(6x+1-6x+1\right)^2=2^2=4\)

b) Ta có: \(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)

\(=2x^3-3x-5x^3-x^2+x^2\)

\(=-3x-3x^3\)

c) Ta có: \(3x\left(x-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)

\(=3x^2-6x-5x+5x^2-8x^2+24\)

\(=24-11x\)

d) Ta có: \(3\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2-1\right)\left(2+1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^2-1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^4-1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^8-1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^{16}-1\right)\left(2^{16}+1\right)\)

\(=2^{32}-1\)

28 tháng 9 2021

\(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(1+6x\right)\left(6x-1\right)\)

\(=\left(6x+1\right)^2-2\left(6x+1\right)\left(6x-1\right)+\left(6x-1\right)^2\)

\(=\left(6x+1-6x+1\right)^2\)

\(=4\)

\(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)

\(=2x^3-3x-5x^3-x^2+x^2\)

\(=\left(2x^3-5x^3\right)+\left(x^2-x^2\right)-3x\)

\(=-3x^3-3x\)

\(3x\left(x-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)

\(=3x^2-6x-5x+5x^2-8x^2+24\)

\(=\left(3x^2+5x^2-8x^2\right)-\left(6x+5x\right)+24\)

\(=-11x+24\)

19 tháng 12 2019

a) \(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(1+6x\right)\left(6x-1\right)\)

\(=36x^2+12x+1+36x^2-12x+1-72x^2+2\)

\(=4\)

c) \(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)

\(=2x^3-3x-5x^3-x^2+x^2\)

\(=-3x^3-3x\)

d) \(3x\left(x-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)

\(=3x^2-6x-5x+5x^2-8x^2+24\)

\(=-11x+24\)

30 tháng 3 2020

a) (6x+1)2 + (6x-1)2 - 2(1+6x)(6x-1)

= (6x+1+6x-1)2 

=144x2

b) x(2x2 -3) - x2(5x+1) +x2

=2x3 - 3x - 5x3 -x2+x2

=-3x3-3x

=-3x(x2+1)

c) 3(22+1)(24+1)(28+1)(216+1)

= (22-1)(22+1)(24+1)(28+1)(216+1)

= (24-1)(24+1)(28+1)(216+1)

= (28-1)(28+1)(216+1)

= (216-1)(216+1)

= 232 -1

d) 3x(x-2) - 5x(1-x) - 8(x2 -3)

= 3x2-6x - 5x + 5x2 - 8x2 +24 

= -11x +24

30 tháng 3 2020

a) = (6x+1)-2(6x+1)(6x-1)+(6x-1)2=(6x+1-6x+1)2=22=4